Determinan Efisiensi Investasi: Pengaruh ESG dan Kinerja Keuangan dengan Harga Saham sebagai Variabel Intervening - Ratna Amalia Nurcahyani; Lies Handrijaningsih (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) factors and financial performance on investment efficiency, with stock price serving as an intervening variable, among conventional banks listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The study is motivated by the growing attention to corporate sustainability practices and the importance of investment efficiency in creating long-term firm value. In addition, this research seeks to examine whether stock prices can function as a mediating mechanism in the relationship between ESG, financial performance, and investment efficiency. This study employs a quantitative research approach using secondary data obtained from annual reports, sustainability reports, and financial statements of conventional banks listed on the IDX. The sampling technique used is purposive sampling based on predetermined research criteria. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through SmartPLS software. The research variables consist of ESG as the independent variable, financial performance proxied by Return on Assets (ROA), investment efficiency as the dependent variable, and stock price as the intervening variable. The results indicate that ESG has a significant effect on stock prices and investment efficiency, while financial performance has a significant effect on stock prices but does not significantly affect investment efficiency. Furthermore, stock prices do not have a significant effect on investment efficiency. The mediation analysis reveals that stock prices are unable to mediate the relationship between ESG and investment efficiency, nor the relationship between financial performance and investment efficiency. These findings suggest that investment efficiency in the banking sector is influenced more by governance quality, risk management, and the direct implementation of ESG practices than by capital market mechanisms reflected through stock prices. This study provides an empirical contribution by extending the literature on the determinants of investment efficiency in the Indonesian banking sector through the integration of sustainability factors (ESG) and financial factors. It also provides evidence that ESG plays a more dominant role than financial performance in influencing investment efficiency, while stock prices have not yet been able to function as an effective mediating mechanism.